2023
DOI: 10.1038/s41417-023-00653-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TLK2 inhibits the progression of gastric cancer by reprogramming amino acid metabolism through the mTOR/ASNS axis

Abstract: Several recent studies suggested that TLKs are related to tumor progression. However, the function and action mechanism of TLK2 in GC remain elusive. We observed that TLK2 was signi cantly upregulated in GC and acted as an independent prognostic factor in GC patients. In line with these results, TLK2 silencing markedly reduced GC aggressiveness, whereas its overexpression had the opposite effect. IP-MS suggested that the effect of TLK2 expression on GC was mainly associated with metabolism reprogramming. TLK2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Overexpressed TLK2 binds to ATF4 to enhance asparagine synthetase (ASNA) transcription level and prevent ubiquitination of ASNA, thus promoting the progression of gastric cancer (GC) by reprogramming amino acid metabolism. Inhibiting TLK2 activity by the mTOR/ASNS axis will result in a suppression of GC cell proliferation and invasion (Wang et al, 2023). These studies showed TLK2 may serve as a potential biomarker for poor prognosis in certain cancers, while its inhibition demonstrates potential for cancer therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Overexpressed TLK2 binds to ATF4 to enhance asparagine synthetase (ASNA) transcription level and prevent ubiquitination of ASNA, thus promoting the progression of gastric cancer (GC) by reprogramming amino acid metabolism. Inhibiting TLK2 activity by the mTOR/ASNS axis will result in a suppression of GC cell proliferation and invasion (Wang et al, 2023). These studies showed TLK2 may serve as a potential biomarker for poor prognosis in certain cancers, while its inhibition demonstrates potential for cancer therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Chromosome instability is one of the earliest genetic changes in precancerous lesions. However, TLK2 overexpression is common in certain tumors, correlating with adverse clinical outcomes (Kim et al, 2016b;Lin et al, 2019;Wang et al, 2023). There are no studies have been reported to explore the effects and possible pathogenesis of TLK2 in HBV-related HCC.…”
Section: Introductionmentioning
confidence: 99%